Randomized Controlled Study of a Remote Flipped Classroom Neuro-otology Curriculum - Carrick, Frederick Robert; Abdulrahman, Mahera; Hankir, Ahmed; Zayaruzny, Maksim; Najem, Kinda; Lungchukiet, Palita; Edwards, Roger A. (Frontiers in Neurology, 2017)
Objective: To test the hypothesis that learning in an online classroom would result in similar outcomes as learning in the traditional classroom when using a flipped classroom pedagogy. Design: Randomized controlled trial. 274 subjects enrolled in a Neuro-otology flipped classroom training program for non Neuro-otologists of 25 hours held over a 3-day period. Subjects were randomized into a “control” group attending a traditional classroom and a “trial” group of equal numbers participating in an online synchronous internet streaming classroom using the Adobe Connect e-learning platform. Main outcome measures: Pre and post multiple choice examinations Methods: All candidates took a pretest examination of the subject material. 2-9 hour and 1-8 hour sessions over 3 consecutive days were given live in the classroom and synchronously in the online classroom using the Adobe Connect e-learning platform. Subjects randomized to the online classroom attended the lectures in a location of their choice and viewed the sessions live on the Internet. A posttest examination was given to all candidates after completion of the course. Two sample unpaired t tests with equal variances were calculated for all pretests and posttests for all groups including gender differences. Results: All 274 subjects demonstrated statistically significant learning by comparison of their pre and posttest scores. There were no statistically significant differences in the test scores between the two groups of 137 subjects each (0.8%, 95% CI 85.45917 to 86.67952; P = 0.9195). 101 Males in the traditional classroom arm had statistically significant lower scores than 72 females (0.8%, 95% CI 84.65716 to 86.53096; P = 0.0377) but not in the online arm (0.8%, 95% CI 85.46172 to 87.23135; P = 0.2176) with a moderate effect size (Cohen’s d = -0.407). Conclusion: The use of a synchronous online classroom in neuro-otology clinical training has demonstrated similar outcomes to the traditional classroom. The online classroom is a low cost and effective complement to medical specialty training in Neuro-Otology. The significant difference in outcomes between males and females who attended the traditional classroom suggests that women may do better than males in this learning environment, although the effect size is moderate.